2023
DOI: 10.1111/eva.13602
|View full text |Cite
|
Sign up to set email alerts
|

Genomic vulnerability of a freshwater salmonid under climate change

Anna Tigano,
Tyler Weir,
Hillary G. M. Ward
et al.

Abstract: Understanding the adaptive potential of populations and species is pivotal for minimizing the loss of biodiversity in this era of rapid climate change. Adaptive potential has been estimated in various ways, including based on levels of standing genetic variation, presence of potentially beneficial alleles, and/or the severity of environmental change. Kokanee salmon, the non‐migratory ecotype of sockeye salmon (Oncorhynchus nerka), is culturally and economically important and has already been impacted by the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Several studies in this Special Issue investigated the crucial role of genomic diversity in maintaining life history variation and enabling natural populations to adapt to local environments. Three papers investigated genomic variation associated with locally adapted traits across populations (Lecomte et al, 2024;Narum et al, 2024;Willis et al, 2024), two others focused on genomic variation to adapt under scenarios of climate change (Tigano et al, 2024) or persist through ecological disturbance (Frei et al, 2024), and another on genomic differences between hatchery reared versus wild stocks (Howe et al, 2024). Lecomte et al (2024) examined SNPs, structural variants (SVs), and small indels between two populations of Atlantic Salmon in North America with differences in life history traits (i.e., age at smoltification and maturity).…”
Section: Adaptive Variation From Whole-genome Resequencing Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in this Special Issue investigated the crucial role of genomic diversity in maintaining life history variation and enabling natural populations to adapt to local environments. Three papers investigated genomic variation associated with locally adapted traits across populations (Lecomte et al, 2024;Narum et al, 2024;Willis et al, 2024), two others focused on genomic variation to adapt under scenarios of climate change (Tigano et al, 2024) or persist through ecological disturbance (Frei et al, 2024), and another on genomic differences between hatchery reared versus wild stocks (Howe et al, 2024). Lecomte et al (2024) examined SNPs, structural variants (SVs), and small indels between two populations of Atlantic Salmon in North America with differences in life history traits (i.e., age at smoltification and maturity).…”
Section: Adaptive Variation From Whole-genome Resequencing Studiesmentioning
confidence: 99%
“…Tigano et al. ( 2024 ) examined the adaptive potential of Kokanee Salmon ( O. nerka ), a non‐migratory ecotype of Sockeye Salmon, in the face of climate change. By integrating analyses of genetic variation, genotype–environment associations, and climate modeling based on genomic data from 224 whole genomes sampled from 22 lakes in Canada, they found that extreme temperatures, particularly warmer temperatures, had the strongest signature of selection in the genome and were the best predictors of adaptive genomic variation.…”
Section: Synopsis Of Articles—advances In Salmonid Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of ongoing environmental changes it is particularly important to consider the possibility of adaptive responses of populations affected by shifting climatic conditions as shown across various study systems [28][29][30][31][32][33] . Species distribution models under various climate change scenarios indicate that many forest tree species will alter their geographical distribution to align with their ecological niche 7,12,[34][35][36] .…”
Section: Introductionmentioning
confidence: 99%